Mapping Sustainable Development Goals Topics and News Values Citizen Journalism on Instagram - Hanief, Lalita; Fatchiya, Anna; Hapsari, Dwi Retno; Pramono, Firdanianty (Jurnal Kajian Jurnalisme, 2026)
Background: Citizen journalism is an alternative form of media that voices marginalized issues in society. The topic of the Sustainable Development Goals (SDGs) is studied as a representation of regional development, supported by news-value elements in citizen-journalism reporting on Instagram. Purpose: Analyze the trend of citizen journalism reporting that represents Sustainable Development Goals (SDGs) by measuring frequency based on topic and news value. Methods: This study uses quantitative content analysis. Results: The research found that the frequency of citizen journalism news with the highest topic of SDGs is SDGs 11, regarding sustainable cities and communities, at 40%; non-SDGs, 32.5%; and SDGs 3, regarding healthy and prosperous life, at 9.9%. Meanwhile, the news values were dominated by bad news, with a percentage of 50.1%. Conclusion: Citizen journalism news on the Instagram accounts @hay.kalimantan and @seputarbanjarbaru is dominated by SDGs 11 on sustainable cities and communities, with a news value of bad news. Implications: Mapping of citizen journalism reporting on both Instagram accounts shows that citizens are actively voicing the SDGs 11 topic, particularly sustainable cities and communities, in the form of information about residential fires, month-long flooding, fallen trees, and road accidents. Instagram has become a channel for democratic public participation in the digital space, as anyone can become a journalist producing news.